Mean-Field and Monte Carlo calculations of phase transitions in a core–shell Ising nanotube - KARIMOU, Mounirou; OKE, Djidjoho Toussaint; HONTINFINDE, Senan Ida Valerie; KPLE, JOËL; HONTINFINDE, FÉLIX (My University, 2023)
A cylindrical Ising nanotube that consists of 3/2 core spins surrounded by 5/2 shell spins is introduced and studied with Mean-Field approximation and Monte Carlo simulations in the presence of crystal and external magnetic fields. The effects of positive and negative interfacial coupling constants on the magnetic properties have been examined. The thermal behaviors of the order parameters and different types of macroscopic instabilities are presented. The model exhibits compensation points, first- and second-order phase transitions. Richer magnetic properties are obtained in the antiferromagnetic core-shell coupling case. In the presence of ferromagnetic interfacial coupling, the simulations sometimes generated long-lived metastable states. These states jumped to stable thermodynamic ones under thermal fluctuations via first-order phase transitions.
Keywords: Ising nanotube; core-shell structure; Mean-field theory; Monte Carlo method; Magnetic field; Phase transitions; Magnetic hysteresis